Germination and storage of rambutan (Nephelium lappaceum L.) seeds - Chin, Hoong Fong (Faculty of Agriculture, University of Malaya, 1975)
Freshly harvested seeds germinated readily producing two-leaved seedlings within 14 days, provided the arilloid of the fruit was removed and the seeds washed. The juice of the arilloid inhibited germination. Seed position at sowing affected emergence and growth of seedlings. If seeds were sown horizontally on the flattened side, normal seedlingswere produced rapidly. Sun-drying for 8 hr killed all seeds within 1 week of storage. OVen-dryingat 30°C produced the same effect. Seeds stored well in moist sawdust or charcoal for 3-4 weeks. They sprouted readily during storage. Unwashed seeds or seeds treated with juice from the arilloid remained viable for 4 weeks in moist sawdust without sprouting